ORGANISATIONAL READINESS FOR ARTIFICIAL INTELLIGENCE ADOPTION : Case Finnish business domain - Paul, Mia (My University, 2020)
There have been major leaps in the artificial intelligence market in recent years, and many organisations have begun to take an interest in artificial intelligence solutions to develop their business. In recent years, the Finnish government has carried out several projects aimed at promoting development related to the utilisation of artificial intelligence and at improving European-wide co-operation in the scientific and business use of artificial intelligence. The purpose of this master's thesis is to explore how large companies perceive their own capabilities in the adoption of artificial intelligence, along with assessing which internal and external elements they consider relevant. To evaluate this topic, this research paper analyses the responses from 13 Finnish organisations through semi-structured interviews. This study uses the Technology-Organisation-Environment (TOE) theory as the research framework through which these issues are addressed. The TOE framework examines the technology available to an organisation, the external environment, and the internal and external characteristics of the organisation. Based on this research, Finnish organisations raise business case and process understanding, cultural aspects, strategic linking and data-related issues as the most relevant elements that have an impact on the adoption of artificial intelligence. There are plenty of commercial outlets discussing the concepts around AI for business, however scientific research is still fairly limited. The aim of this master's thesis is to narrow this research gap by approaching the topic in a structured manner, hopefully also arousing interest in further research.

Tekoälymarkkinoilla on viime vuosina tapahtunut suuria loikkauksia, ja monissa yrityksissä on yhä enenevässä määrin kiinnostuttu tekoälyratkaisuista liiketoiminnan kehittämiseen. Suomen valtio on viime vuosina julkaissut useita hankkeita, joilla on pyritty edistämään tätä tekoälyn hyödyntämiseen liittyvää kehitystä, sekä parantamaan euroopanlaajuista yhteistyötä tekoälyn saralla niin tieteessä kuin liikemaailmassakin. Tämän Pro Gradu-työn tarkoituksena on tutkia, miten suomalaiset suuryritykset kokevat omat valmiutensa tekoälyn käyttöönotossa, selvittämällä mitä organisaation sisäisiä sekä ulkoisia elementtejä he pitävät relevantteina. Aiheen arvioimiseksi tässä tutkimuksessa analysoidaan 13 suomalaisen organisaation vastauksia teemahaastatteluiden avulla. Tässä tutkimuksessa käytetään teknologian, organisaation ja liiketoimintaympäristön puitteita (TOE-framework) viitekehyksenä, jonka kautta näitä kysymyksiä tarkastellaan. TOE-viitekehys tarkastelee organisaation käytettävissä olevaa teknologiaa, ulkoista liiketoimintaympäristöä, sekä organisaation sisäisiä ja ulkoisia ominaisuuksia. Tämän tutkimuksen perusteella suomalaiset organisaatiot nostavat liiketoimintalähtöisyyden sekä prosessiymmärtämisen, organisaatiokulttuurin osa-alueet, strategisen linkittämisen sekä dataan liittyvät ongelmat keskeisimmiksi elementeiksi, joilla on vaikutusta tekoälyn käyttöönottoon. Liiketoiminnan edistämistä tekoälyratkaisujen avulla on käsitelty paljon mm. kaupallisilla artikkeleilla, mutta riippumattomia tieteellisiä tutkimuksia on tällä hetkellä rajoitetusti saatavilla. Tämän Pro Gradu-työn tavoitteena on kaventaa tätä tutkimusaukkoa lähestymällä aihetta jäsennellyllä tavalla, toivottavasti herättäen kiinnostusta myös lisätutkimuksiin aiheesta.
Keywords: AI adoption, TOE framework theory, technology-environment-organisation, business use case, Tekoäly, use cases, TOE framework, TOE-viitekehys, liiketoiminnan tarpeet